Effects of thinning on the structure of soil microbial communities in a subtropical secondary evergreen broad-leaved forest - Yao, Liangjin; Jiao, Jiejie; Wu, Chuping; Jiang, Bo; Fan, Lili (Frontiers in Plant Science, 2024)
Thinning is a common practice to enhance tree growth, but its effect on rhizosphere soil microorganisms in subtropical secondary evergreen broad-leaved forests remains unclear. This study used 16S rDNA amplicon sequencing to explore soil microflora of fives shrubs and five tree species. The results showed: Thinning altered nutrient distribution and pH in rhizosphere soil, impacting microbial richness, which varied by tree species. The dominant bacterial phyla were Acidobacteria, Proteobacteria, Actinobacteria, and Firmicutes. Although the dominant microbial species remained largely unchanged, thinning increased the relative abundance of Firmicutes. Thinning intensity between 10-15% significantly altered the structure of soil microbial communities., demonstrating species-specific responses. These changes in microbial structure may influence tree growth. This study proposed the potential effects of thinning on rhizosphere soil microorganisms and suggests future research to investigate the specific microbial mechanisms affected by thinning.